2020
DOI: 10.1016/j.jvscit.2020.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Renovascular hypertension secondary to renal artery compression by diaphragmatic crura

Abstract: Median arcuate ligament syndrome is the result of celiac axis compression by the diaphragmatic crura. Although the celiac artery is the most common vessel to have compression, the renal arteries may also rarely be compressed by the crural fibers of the diaphragm, which may cause secondary hypertension. We present two cases of renovascular hypertension secondary to renal artery compression by the diaphragmatic crura. The first patient was treated with open decompression and wide resection of the crural fibers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…RVH can be caused by renal artery compression by extrinsic masses, e.g., Wilms' tumor, neuroblastoma, renal cysts, or diaphragmatic crura [8,26]. To the best of our knowledge, this is the first reported case of RVH caused by renal artery displacement and compression by dysfunctive urinary bladder.…”
Section: Discussionmentioning
confidence: 87%
“…RVH can be caused by renal artery compression by extrinsic masses, e.g., Wilms' tumor, neuroblastoma, renal cysts, or diaphragmatic crura [8,26]. To the best of our knowledge, this is the first reported case of RVH caused by renal artery displacement and compression by dysfunctive urinary bladder.…”
Section: Discussionmentioning
confidence: 87%
“…Due to its rarity, literature describing hypertension secondary to diaphragmatic compression on the renal vessels is limited, with only 23 cases reported by a recent review. The review also showed that among cases reported, almost 48% (11) had left-sided compression, almost 17% (4) had right-sided compression, 13% (3) cases were bilateral, and the rest were unknown [ 7 ]. Our patient had a right-sided renal artery indentation by the diaphragmatic crus.…”
Section: Discussionmentioning
confidence: 99%